Association of Plasma Atherogenic Index (PAI) with arterial stiffness in normotensive versus hypertensive Patients - Ain, Qurat Ul; Younas, Muhammad; khan, Muhammad Qaisar Alam; Niaz, Ayesha; Haroon, Zujaja Hina; Anwar, Muhammad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To find Association of Plasma Atherogenic Index with Arterial stiffness in normotensive and hypertensive patients.Study Design: Diagnostic Accuracy Study.Place and Duration of Study: Armed Forces Institute of Cardiology (AFIC) and Department of Chemical Pathology, Armed Forces Institute of Pathology (AFIP), Rawalpindi Pakistan, from Oct 2022 to May 2023.Methodology: Hypertensive and normotensive patients with age group of 30-50 years were included in this study. Semi-structured Questionnaire was structured to collect the information regarding demographics, any comorbidity and medication history.Results: Total 140 subjects were included in current research at AFIC. Altogether, 92(65.7%) male and 48(34.3%) female were participated. Plasma Atherogenic Index (PAI) is derived Index used for current study and it is divided into low risk (0.1), Intermediate risk (0.1-0.24) and high risk (>0.24). Out of all patients 13(9.3%) were in low risk, 38(27.1%) were in intermediate risk and 89(63.6%) were in high risk category. For association between PWV and PAI with blood pressure computed results showed significant association with p-value